Double‐ and triple‐duty actions in childhood for addressing the global syndemic of obesity, undernutrition, and climate change: A scoping review. (8th February 2023) - Venegas Hargous, Carolina; Strugnell, Claudia; Allender, Steven; Orellana, Liliana; Corvalan, Camila; Bell, Colin
Summary: Obesity, undernutrition, and climate change constitute a global syndemic that disproportionately affects vulnerable populations, including children. Double‐ and triple‐duty actions that simultaneously address these pandemics are needed to prevent further health, economic, and environmental consequences. Evidence describing the implementation and evaluation of such actions is lacking. This review summarized the literature on whole‐of‐population actions targeting children that were designed or adapted to be double or triple duty. Six academic databases were searched (January 2015–March 2021) using terms related to 'children', 'intervention', 'nutrition', 'physical activity', and 'climate change'. Data were extracted from 43/15, 475 studies, including six randomized controlled trials. Most (58%) described triple‐duty actions targeting food systems in schools such as implementing guidelines for healthier and environmentally sustainable school meals programs, and 51% reported engaging community in the design, implementation, and/or evaluation of actions. Changes in dietary intake, diet composition, greenhouse gas emissions, and food waste were the most frequently reported outcomes and 21 studies (three randomized controlled trials) showed positive double‐ or triple‐duty effects. This review is the first to demonstrate that double‐ and triple‐duty actions for addressing the global syndemic in childhood have been implemented and can have a positive impact on obesity, undernutrition, and climate change.